Measurement of Activated Factor IX in Factor IX Concentrates: Correlation with In Vivo Thrombogenicity - Gray, Elaine; Tubbs, Jill; Thomas, S; Oates, A; Boisclair, M; Kemball-Cook, G; Barrowcliffe, T W (Thrombosis and Haemostasis, 1995)
Current in vitro tests for thrombogenicity of FIX concentrates used for prothrombin complex concentrates (PCCs), are of little value when applied to high purity FIX (HP FIXs). In the present study, we have developed a chromogenic assay for activated FIX (FIXa) and evaluated its ability to predict in vivo thrombogenic potential of HP FIXs in a modified Wessler stasis model. Among the HP FIXs, only 1 out of 7 products had no detectable FIXa; this product also showed no in vivo thrombogenicity. In the other 6 products, FIXa content ranged from 0.15–1.2 U/1000 iu FIX, and all showed some evidence of in vivo thrombogenicity, with mean thrombus scores ranging from 0.25–4. There was a significant positive correlation (r = 0.55, p <0.02) between FIXa levels and in vivo thrombogenicity of HP FIXs. NAPTT data were not significantly correlated with the in vivo results and the TFCT also showed no direct correlation with the mean thrombus score. These results indicate that HP FIXs may still carry a small residual thrombotic risk and measurement of FIXa content of these products may be a better predictor of thrombogenicity than the current in vitro tests.